2009
DOI: 10.1111/j.1365-2125.2009.03519.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for oxazepam as an in vivo probe of UGT2B15: oxazepam clearance is reduced by UGT2B15 D85Y polymorphism but unaffected by UGT2B17 deletion

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• UDP-glucuronosyltransferase (UGT) 2B15 is a major drug glucuronidation enzyme expressed in human liver.• Oxazepam is an isoform-selective probe drug that is being used for in vitro studies of UGT2B15.• The most common UGT2B15 missense polymorphisms (D85Y and K523T) are correlated with variable oxazepam glucuronidation in human liver bank samples.• UGT2B17 is also expressed in liver and has high sequence homology and substrate specificity overlap with UGT2B15. WHAT THIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 27 publications
2
45
0
1
Order By: Relevance
“…Previous work from our lab identified SNP D85Y (253G>T, rs1902023) in exon 1 of the UGT2B15 gene [13]. Moreover we demonstrated that the high frequency variant allele D85Y (allele frequency 47%) was a major determinant of the observed inter-individual variability ofoxazepam glucuronidation in vivo [14]. However, SNP D85Y could explain only 34% of the observed interindividual variability of hepatic oxazepam glucuronidation in vivo [14].…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…Previous work from our lab identified SNP D85Y (253G>T, rs1902023) in exon 1 of the UGT2B15 gene [13]. Moreover we demonstrated that the high frequency variant allele D85Y (allele frequency 47%) was a major determinant of the observed inter-individual variability ofoxazepam glucuronidation in vivo [14]. However, SNP D85Y could explain only 34% of the observed interindividual variability of hepatic oxazepam glucuronidation in vivo [14].…”
Section: Introductionmentioning
confidence: 63%
“…Moreover we demonstrated that the high frequency variant allele D85Y (allele frequency 47%) was a major determinant of the observed inter-individual variability ofoxazepam glucuronidation in vivo [14]. However, SNP D85Y could explain only 34% of the observed interindividual variability of hepatic oxazepam glucuronidation in vivo [14]. Consequently, other trans -acting factors could regulate UGT2B7 and UGT2B15 expression and contribute to this variability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…UGT1A7, which was observed here to glucuronidate R-lorazepam, also metabolized R-oxazepam. Court et al (2004) and He et al (2009) subsequently showed that Slorazepam, but not R-lorazepam, glucuronidation activity was reduced in HLM from donors expressing UGT2B15*2, and the apparent oral clearance of oxazepam was reduced in subjects homozygous for UGT2B15*2. Overall, the UGT2B15*2 allele was estimated to account for 34% of the interindividual variability in oxazepam clearance (He et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Court et al (2004) and He et al (2009) subsequently showed that Slorazepam, but not R-lorazepam, glucuronidation activity was reduced in HLM from donors expressing UGT2B15*2, and the apparent oral clearance of oxazepam was reduced in subjects homozygous for UGT2B15*2. Overall, the UGT2B15*2 allele was estimated to account for 34% of the interindividual variability in oxazepam clearance (He et al, 2009). The differential effects of inhibitors on R-and S-oxazepam glucuronidation by HLM further support the involvement of different UGT enzymes in the glucuronidation of the oxazepam enantiomers (Patel et al, 1995b).…”
Section: Discussionmentioning
confidence: 99%